Innovation and Social Entrepreneurship in Tourism A Potential for Local Business Development - HeLge Tetzschner; Henrik Herlau (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
Over the past few years, the tourist industry has come to be recognised as a way of providing strategic support for sustainable local business development. In this article we attempt to define an appropriate innovation concept in relation to tourism on the basis of an attractor principle. We then discuss the concept of entrepreneurship in connection with tourism, looking at its significance in its relationship with local business development, thereby positing the premise of social entrepreneurship. This frame of reference is used in five cases in the analysis. The analysis shows that it is possible to innovate and draw up plans for new attractors but that it is considerably more difficult to convert these plans into reality through social entrepreneurship. The conclusion is that we need to focus upon organisation of semi-public tourist organisations, if we want tourism to promote local business development.
Keywords: 330; Tourismuswirtschaft; Gemeindeentwicklung; Unternehmenserfolg; Dänemark